JOURNAL OF GOVERNMENT & POLITICS : Political Family and Intra-party Democracy in Indonesia (A Study on the Political Recruitment of the Golkar Party during the reform Era in South Sulawesi) - Titin Purwaningsih , Valina Singka Subekti (FISIPOL UMY, 2017)
This paper looks at the political family involved in the local politics in South Sulawesi.